1999
DOI: 10.1111/j.1745-459x.1999.tb00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pasteurization on the Sensory Characteristics of a Ewe's‐milk Cheese

Abstract: The present study examined the effect of two different processing technologies in the manufacture of a ewe's-milk cheese. Two batches were manufactured, one from raw milk, the other from pasteurized milk. A starter culture consisting of Lactococcus lactis subsp. lactis var. diacetylactis and Lactobacillus casei subsp. casei was added to both batches. Descriptive analysis of the sensory characteristics was carried out for the two cheese batches at two different ripening times (90 and 180 days).Statistical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…Most French cheeses made from raw milk had higher scores for “goaty,”“fermented,”“sharp‐bite” and “bitter.” The high scores for these attributes might be explained by the occurrence of more chemical degradation during the ripening of raw‐milk cheeses. These findings are in accordance with Mendia et al. (1999), who found that a ewe's milk cheese made from raw milk was more pungent.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Most French cheeses made from raw milk had higher scores for “goaty,”“fermented,”“sharp‐bite” and “bitter.” The high scores for these attributes might be explained by the occurrence of more chemical degradation during the ripening of raw‐milk cheeses. These findings are in accordance with Mendia et al. (1999), who found that a ewe's milk cheese made from raw milk was more pungent.…”
Section: Resultssupporting
confidence: 92%
“…(2000) reported that the use of pasteurized milk in a Greek cheese, Anevato, resulted in a lack of the characteristic flavor of the cheese. Mendia et al. (1999) studied Idiabazal‐type cheese from ewe's milk and found that raw‐milk cheese was more pungent and salty, while pasteurized‐milk cheese generally was creamier and sweeter.…”
Section: Introductionmentioning
confidence: 99%
“…Idiazabal cheesemakers usually coagulate the milk with locally produced lamb rennet paste, whereas Manchego and Roncal cheesemakers usually coagulate the milk with commercial bovine rennet, and Zamorano cheese makers use commercial liquid lamb rennet. Numerous studies have reported changes in sensory properties of cheese due to changes in raw milk microflora (Mendı´a, Iba´n˜ez, Torre, & Barcina, 1999), in milk composition mainly by animal feeding (Buchin, Martin, Dupont, Bornard, & Achilleos, 1999), seasonal factors (Cha´varri, et al, 1999;Mendı´a, Iba´n˜ez, Torre, & Barcina, 2000;Ferna´ndez-Garcı´a, Serrano, & Nu´n˜ez, 2002b;Mun˜oz, Ortigosa, Torre, & Izco, 2003) and technological processes such as pasteurisation (Cha´varri et al, 2000;Ortigosa, Torre, & Izco, 2001;Ferna´ndez-Garcı´a, Carbonell, & Nu´n˜ez, 2002a) or micro-filtration (Bouton & Grappin, 1995) of milk, or use of different animal rennet (Virto et al, 2003) and starter culture (Ba´rcenas, Pe´rez-Elortondo, & Albisu, 2003). Also, different authors have studied relationships between chemical composition, particularly the volatile composition, and sensory properties such as flavour and odour of the cheese (Lawlor, Delahunty, Wilkinson, & Sheehan, 2002;Lawlor, Delahunty, Sheehan, & Wilkinson, 2003;Pinho, Ferreira, & Ferreira, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In industrial cheese production pasteurization of raw milk has been reported to affect cheese aroma type and intensity, depending on the type of treatment used (35,39). Besides destroying pathogenic bacteria, pasteurization also influences the type of lactic acid bacteria present during ripening (34) and therefore can adversely affect flavor development.…”
mentioning
confidence: 99%
“…To overcome losses in flavor and aroma produced by beneficial microorganisms destroyed by heating, alternative strategies have been suggested or tested. Either selected thermoresistant strains or strains (natural or mutant) with high levels of endogenous lipolytic and/or proteolytic activities have been used as starters or adjuncts for fermentation (1,34,35,42,43). Recently, enzymes with key activities, alone or in combination with starters, have been used to enhance cheese flavor (10,(21)(22)(23)45).…”
mentioning
confidence: 99%